2009
DOI: 10.1007/s00432-009-0698-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of cucurbitacin E on pancreatic cancer cells growth via STAT3 signaling

Abstract: Our results suggested that cucurbitacin E may be an effective regimen for the chemotherapy of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 31 publications
(32 reference statements)
0
40
0
Order By: Relevance
“…Regarding pancreatic cancer, the work of Sun et al (2010) showed that cucurbitacin E of the family of triterpenoids isolated from plants can reduce the phosphorylation of STAT3, leading to inhibition of cell growth, increased expression of p53 and induction of apoptosis of cancer cells. Indeed, p53 can arrest cell cycle progression at different points and induce apoptosis of cells whose growth has become uncontrolled.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Regarding pancreatic cancer, the work of Sun et al (2010) showed that cucurbitacin E of the family of triterpenoids isolated from plants can reduce the phosphorylation of STAT3, leading to inhibition of cell growth, increased expression of p53 and induction of apoptosis of cancer cells. Indeed, p53 can arrest cell cycle progression at different points and induce apoptosis of cells whose growth has become uncontrolled.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…However, the same research group described that the effects of cucurbitacin B on K562 leukemia cells were related to the inhibition of STAT-3 expression (Chan et al, 2010b). Another recent work on the effects of cucurbitacin E on pancreatic cells demonstrated an association with inhibition of STAT 3 (Sun et al, 2010). The STAT proteins have dual roles as cytoplasmic signaling proteins and nuclear transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports attributed in vitro and in vivo anticancer activities to the cucurbitacins (Fang et al, 1984;Duncan et al, 1996;Chan et al, 2010a;Sun et al, 2010). Jayaprakasam and co-workers demonstrated the cytotoxic properties of cucurbitacins B, D, E and I, isolated from the fruits of Cucurbita andreana, against colon, breast, lung and central nervous system cancer cell lines (Jayaprakasam et al, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…Recently, several triterpenoids from various plants have been reported to feature antiproliferative [51][52][53] and anti-invasive [54,55] bioactive components. More than 50 triterpenoids have been isolated from bitter melon, but their biological activities have yet to be explored in detail.…”
Section: Phytochemicals and Cucurbitane Triterpenoidsmentioning
confidence: 99%